مميزات المنهج الدعوي عند الداعية عبد الرحمن السميط - عماري, يعقوب (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: تتناول أطروحة الدكتوراه الموسومة بمميزات المنهج الدعوي عند الداعية عبد الرحمن السميط التجربة الدعوية التي خاضها الداعية السميط في أدغال إفريقيا، وتهدف الدراسة لاستقصاء المنهج الذي اعتمده الداعية السميط في دعوته إلى الله ومقارنته بمنهج سابقيه من الدعاة، كما تسعى الدراسة لمعرفة أهم مميزاته مقارنة ببقية المناهج الدعوية المعروفة. كما تناولت مفهوم الدعوة إلى الله وكيف أثر على رؤية السميط الدعوية، وكيف كانت القارة السمراء قبل مجيء السميط وكيف أصبحت بعد عمله بها، وهل كان له تأثير ملموس وواضح في المجال الدعوي من خلال الاحصائيات المقدمة من طرف الجمعية الدعوية التابعة له والتي أسسها لهذا الغرض تحديدا. ثم تحدثت عن كيفية تنظيم الداعية السميط للدعوة إلى الله من خلال العمل المؤسسي وهيكلتها بشكل منظم يتيح استمرارية العمل بغض النظر عن بقاء الداعية السميط أو رحيله. وفي نهاية الأطروحة سأعرض للنتائج التي تحققت بعد المجهودات الدعوية المبذولة من طرف الداعية السميط وجمعيته، ناهيك عن استخلاص أهم النقاط العملية التي تفيد الدعاة في المستقبل، ومدى إمكانية تكرار تجربته في مكان آخر حول العالم مع الأخذ بالمتغيرات الموجودة وخصوصية كل ثقافة لدى مختلف الأجناس. وفي الختام سأوضح الآفاق المستقبلية للدعوة إلى الله في ظل التغيرات العالمية الراهنة وكيف يمكن للإسلام التعايش مع التحديات الثقافية والسياسية التي تواجهه. فرنسية أو انجليزية: Résumé The following doctoral thesis tagged with the features of the advocacy curriculum of the preacher Abd Al-Rahman Al-Sumait deals with the missionary experience that he underwent in the Africa jungles, the study aims to investigate the methodology that he adopted in his call to Allah and compare it with the previous preaching methodologies, the study also seeks to know its most important features compared to the rest of the known advocacy curricula. It also dealt with the concept of the call to Allah and how it affected Al-Sumait's view of it, And how the brown continent was before his arrival and how it became after his work in it, And if he had a concrete and a clear impact in the advocacy field through the statistics provided by the advocacy association, which he established for this purpose specifically. Then I talked about how the preacher organized the call to Allah through institutional work and structured it in a systematic way that allows the continuity of work regardless to his presence or absence. At the end of the thesis, the results that have been achieved after the advocacy efforts made by the preacher Al-Sumait and his association will be presented, beside the extraction of the most important practical points that benefit the preachers in the future, and the possibility of replicating his experience in other places around the world, with the consideration to the existing variables and the peculiarity of each culture. In conclusion, I will explain the future prospects for the call to Allah in light of the current global changes and how Islam can coexist with the cultural and the political challenges facing it.
أطروحة دكتوراه تخصص الدعوة و الثقافة الإسلامية في العلوم الإسلامية
Keywords: مميزات المنهج الدعوي عند الداعية عبد الرحمن السميط; advocacy, Africa, Abd al Rahman al sumait, advocacy curriculum, relief work